PENGARUH FIXED ASSET TURNOVER, UMUR PERUSAHAAN DAN FAKTOR LAINNYA TERHADAP MANAJEMEN LABA - Taaj Rania Maricar; Yuliani Almalita (E-Jurnal Akuntansi TSM, 2022)
The purpose of this study is to get empirical evidence about influence of institutional ownership, managerial ownership, firm size, firm age, leverage, profitability, fixed asset turnover, and proportion of independent commissioner on earnings management in manufacturing companies listed in Indonesia Stock Exchange. The object of this research are manufacturing companies listed in Indonesia Stock Exchange during 2018-2020. Selection of sample is using purposive sampling method, where there are 72 companies with 216 data that meet the sample selection criteria. Research data is analyzed with multiple regression analysis. The results of this study indicate that firm size has a negative effect on earning management because big companies can get easy funds from external and internal so they can minimize earnings management. Firm age has negative effect on earnings management because the new company was difficult to get funds so they do earnings management. Leverage has positive effect on earnings management because high leverage means company has insolvable fund. Profitability has positive effect on earnings management because management want to minimalize fluctuations in profit and taxes. Fixed asset turnover has negative effect on earnings management because management want to disclose the company’s ability to utilize fixed asset. While institutional ownership, managerial ownership, and proportion of independent commissioner have no influence on earnings management.